Middle Pleistocene ecology in central Italy. New isotopic insights from fauna tooth enamel of Casal de’ Pazzi (Rome, Italy) - Briatico, Giuseppe; Bocherens, Hervé (Journal of Mediterranean Earth Sciences, 2023)
The late Middle Pleistocene site of Casal de’ Pazzi is one of the numerous archaeological and paleontological sites found in central Italy. It yielded a rich fossil collection, including Middle Paleolithic stone tools and a single retouched bone fragment, faunal remains, a parietal fragment attributed to Homo heidelbergensis (or likely ascribed to a Neanderthal hominin), and leaf fossil impressions of Zelkova sp., Laurus nobilis, and Cercis siliquastrum. We investigated stable carbon and oxygen isotopes (δ13C and δ18O) of tooth enamel from the mammal assemblage of Casal de’ Pazzi to reconstruct their diet and habitat and to contribute to the understanding of the Middle Pleistocene environment in central Italy. We analyzed the isotopic composition of tooth enamel of several taxa, including Palaeoloxodon antiquus, Bos primigenius, Stephanorhinus kirchbergensis, Equus ferus, Dama dama and, for the first time in Europe, Hippopotamus amphibius. Isotopic analyses indicate that mammals exploited different habitats within a C3 mosaic landscape with closed and open environments. This is consistent with leaf fossil impressions found at Casal de’ Pazzi, and pollen data from the nearby lake of Valle di Castiglione, which indicated that the Casal de’ Pazzi area was characterized by riparian habitats and diversified wooded/forested vegetation with extended grasslands. Comparisons with published isotopic data from central Italy between ~600 ka and ~171 ka provided evidence for considerable environmental differences through time and space, according to trends in the local vegetation and general climate.